Contour prognostic model for predicting survival after resection of colorectal liver metastases: development and multicentre validation study using largest diameter and number of metastases with RAS mutation status. Issue 8 (7th April 2021) - Kawaguchi, Y; Kopetz, S; Tran Cao, H S; Panettieri, E; De Bellis, M; Nishioka, Y; Hwang, H; Wang, X; Tzeng, C -W D; Chun, Y S; Aloia, T A; Hasegawa, K; et al.
Abstract: Background: Most current models for predicting survival after resection of colorectal liver metastasis include largest diameter and number of colorectal liver metastases as dichotomous variables, resulting in underestimation of the extent of risk variation and substantial loss of statistical power. The aim of this study was to develop and validate a new prognostic model for patients undergoing liver resection including largest diameter and number of colorectal liver metastases as continuous variables. Methods: A prognostic model was developed using data from patients who underwent liver resection for colorectal liver metastases at MD Anderson Cancer Center and had RAS mutational data. A Cox proportional hazards model analysis was used to develop a model based on largest colorectal liver metastasis diameter and number of metastases as continuous variables. The model results were shown using contour plots, and validated externally in an international multi-institutional cohort. Results: A total of 810 patients met the inclusion criteria. Largest colorectal liver metastasis diameter (hazard ratio (HR) 1.11, 95 per cent confidence interval 1.06 to 1.16; P < 0.001), number of colorectal liver metastases (HR 1.06, 1.03 to 1.09; P < 0.001), and RAS mutation status (HR 1.76, 1.42 to 2.18; P < 0.001) were significantly associated with overall survival, together with age, primary lymph node metastasis, and prehepatectomy chemotherapy. The model performed well in the external validation cohort, with predicted overall survival values almost lying within 10 per cent of observed values. Wild-type RAS was associated with better overall survival than RAS mutation even when liver resection was performed for larger and/or multiple colorectal liver metastases. Conclusion: The contour prognostic model, based on diameter and number of lesions considered as continuous variables along with RAS mutation, predicts overall survival after resection of colorectal liver metastasis. Abstract : A prognostic model that incorporated largest diameter and number of colorectal liver metastases as continuous variables along with RAS mutation status performed well in the development cohort and an external cohort. This model permits calculation of a specific survival probability for each patient and may help in clinical decision-making.